Preparation method of porous electrode, porous electrode and application of porous electrode
By using the first etching, hole filler leveling treatment and second etching methods in the battery production process, low tortuosity porous electrodes are prepared, which solves the problem of slow ion transmission speed in the thick electrode structure and realizes the battery Efficient preparation and performance improvement.
Patent Information
- Application Number
- CN202411662905.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to realize the continuous batch preparation of low tortuosity aperture structures in thick electrode structures in battery production processes, resulting in slow ion transmission speed, limiting the capacity, magnification and cycling performance of the battery.
Through the coordinated cooperation of the first etching, the pore filler leveling treatment and the second etching, a porous electrode with low tortuosity was prepared to ensure that the electrode was not damaged during the subsequent processing, and the continuous batch preparation of the battery was achieved.
The preparation of low-towing porous electrodes is realized, the ion transmission speed of the battery is improved, the capacity, magnification and cycling performance are improved, and it is suitable for actual battery production processes and can achieve batch production.
Smart Images

Figure CN119480922A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a preparation method of a porous electrode, a porous electrode and applications thereof. Background Art
[0002] In order to meet the growing energy demand of portable electronic devices and electric vehicles, it is crucial to develop high-performance batteries (such as lithium-ion batteries or sodium-ion batteries) with high energy density and fast charging capabilities. At present, there are three main ways to improve the energy density of batteries from the perspective of material systems: (1) Develop new high-capacity battery systems, such as lithium-sulfur batteries and lithium-air batteries, but new high-capacity systems still face huge challenges and require a long period of development; (2) Develop high-voltage positive electrodes, such as high-voltage lithium cobalt oxide, ternary layered positive electrodes, lithium-rich manganese-based positive electrodes, etc. High-voltage positive electrodes can greatly improve the energy density of batteries, but their poor cycle stability and extremely high requirements for electrolytes and binders limit their development; (3) Design thick electrode architectures (20-25 mg / cm 2 Double-sided surface density), that is, increasing the content of active materials per unit volume of the battery without changing the battery chemical system, thereby increasing the energy density of the battery system. Compared with the first two approaches, the thick electrode architecture has the advantage of being compatible with various electrode materials. Therefore, improving the energy density of the battery through the thick electrode architecture design has received widespread attention.
[0003] However, the reaction kinetics in thick electrodes (thickness of the electrode layer on one side ≥ 100μm) are inevitably delayed due to the extension of the charge transfer path. Especially at higher rates, slow charge transfer becomes a key factor limiting the fast charging capability and energy density improvement of the battery cell. Thick electrode design requires higher electron and ion transfer rates in the electrode to achieve the same charge / discharge rate performance as thin electrodes. Therefore, in order to improve electrolyte wettability and lithium ion transfer rate, low tortuosity pore design is the key principle of thick electrode design.
[0004] At present, the preparation methods of thick electrodes that reduce tortuosity and improve electrolyte wettability and lithium ion transfer rate are as follows: (1) Preparation of low tortuosity electrodes using an external magnetic field. Billaud et al. coated Fe3O4 nanoparticles on the surface of graphite sheets and loaded an external magnetic field during the electrode coating process. The graphite sheets were distributed perpendicular to the current collector, and the pore tortuosity in the thickness direction of the electrode was reduced by 4 times, which improved the electrochemical performance of the prepared battery. (2) Directed freeze-drying processing to prepare low tortuosity electrodes. For example, Hamamoto et al. used gel freezing to prepare high-porosity LFP / C composite electrodes. The pores were vertically distributed and the pore size could be controlled by adjusting the freezing temperature. Behr et al. also used directional freezing to prepare LiN i0.8 Co 0.15 Al0.05 O2 electrode, the prepared electrode has directional straight-through holes and low pore tortuosity, which realizes the control of the electrode pore morphology and has a high lithium ion transmission rate. (3) Extrusion preparation of low tortuosity electrodes, such as Bae et al. use extrusion sintering method to prepare electrodes. First, the active material, conductive agent and binder are mixed to prepare rods, and then the rods are squeezed and compressed through a mold to become thinner. The extruded rods are arranged to form rods and then squeezed and compressed again, and repeated several times. Finally, the binder is sintered to remove the binder, and an electrode with a thickness of 220μm and a vertical pore of about 6μm is prepared. The prepared electrode has high surface capacity and good rate performance. In addition, there are also improved methods such as 3D printing to prepare low tortuosity electrodes, template processing to prepare low tortuosity electrodes, and laser processing to prepare low tortuosity electrodes. Although the above method obtains a low-tortuosity pore structure, it is not combined with the actual production process of power / energy storage lithium batteries to ultimately realize the manufacture of the battery. It simply reduces the tortuosity by preparing the electrodes of power / energy storage lithium batteries. When the thick electrodes are subsequently processed, the pore structure will be destroyed. It cannot be used in actual processing, and the cost is extremely high, and continuous production cannot be achieved.
[0005] Therefore, how to achieve the tortuosity of the aperture structure in the degraded thick electrode structure and be suitable for the production and processing of the actual electrode structure is a problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a porous electrode, a porous electrode and its application. The preparation method provided by the present invention truly realizes the preparation of an electrode with a low-tortuosity pore structure, thereby realizing the continuous batch preparation of batteries with low-tortuosity electrodes, which is operable and efficient, and solves the problem of poor capacity, rate and cycle performance of current thick electrodes due to ion transport limitations.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a porous electrode, the preparation method comprising the following steps:
[0009] Performing a first etching on at least one side of the electrode current collector to obtain an electrode current collector having holes;
[0010] Filling the holes in the electrode current collector with a pore-filling agent, and performing a second etching on the area of the electrode current collector that does not contain the pore-filling agent after the filling treatment, so that the electrode current collector has a surface pore-filling agent protrusion, thereby obtaining an electrode current collector to be used;
[0011] Coating the surface of the electrode current collector to be used with electrode slurry to obtain an electrode to be treated;
[0012] The pore-filling agent is removed from the electrode to be processed to obtain the porous electrode.
[0013] The preparation method provided by the present invention, through the coordinated cooperation of the first etching, the filling treatment and the second etching, obtains a hole structure with a non-through structure along the thickness direction of the electrode current collector after the first etching, and after the hole filling treatment of the hole filling agent, the area in the electrode current collector that does not contain the hole filling agent is subjected to the second etching, thereby obtaining a hole filling agent protrusion with strong ductility and compressive resistance, which will not collapse even after electrode slurry coating and subsequent electrode preparation treatment processes. After removing the hole filling agent, the hole structure with low tortuosity is retained, and the preparation of low-tortuosity porous electrodes is truly realized, which is operable and efficient, and can also be mass-produced, solving the problems of capacity, rate and cycle performance of thick electrodes caused by ion transport limitations; and the preparation method is suitable for actual battery production processes, and the shape and size of the electrodes are controllable.
[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] Preferably, after the second etching is performed so that the electrode current collector has surface pore-filling agent protrusions, the surface is reversely filled and leveled to obtain the electrode current collector to be used.
[0016] After the surface of the electrode current collector with the surface pore-filling agent protrusions is reversely filled and leveled, the pore-filling agent protrusions can be prevented from being damaged during the process of rolling up and reprocessing the electrode current collector.
[0017] Preferably, the electrode current collector to be used for reverse filling treatment is first subjected to bottom cleaning treatment to expose the pore-filling agent protrusions, and then electrode slurry is coated to obtain the electrode to be treated.
[0018] In the present invention, the bottom cleaning treatment is used to remove the materials on the filling surface except the pore-filling agent protrusions during reverse filling, thereby exposing the pore-filling agent protrusions again for the subsequent preparation of the porous electrode structure.
[0019] Preferably, when both sides of the electrode current collector have surface pore-filling agent protrusions, the preparation method comprises:
[0020] Firstly, the surfaces of both sides of the electrode current collector are subjected to a first etching and a filling treatment respectively, and then the surface of one side is subjected to a second etching to obtain an electrode current collector having a protrusion of a pore-filling agent on one side of the surface, and then the side surface is subjected to a reverse filling treatment to obtain an electrode current collector having a reverse filling plane on one side;
[0021] Then, the other side surface of the electrode current collector is further etched for a second time to obtain a hole-filling agent protrusion on the other side surface, and then the side surface is reversely filled and flattened to obtain an electrode current collector with reverse-filled flat surfaces on both sides;
[0022] The electrode current collector with reverse filling planes on both sides is used as the electrode current collector to be used, and the bottom of one side surface is firstly cleaned and the electrode slurry is coated, and then the bottom of the other side surface is cleaned and the electrode slurry is coated on the other side surface to obtain the electrode to be processed;
[0023] The pore-filling agent is removed from the electrode to be processed to obtain the porous electrode.
[0024] When the porous electrode provided by the present invention is a double-sided coating structure, the pore filler protrusions on one side of the surface are first prepared, and after the reverse filling treatment of the side surface is performed, it is avoided that the original pore filler protrusions on one side of the surface are destroyed when the other side is treated; further, the electrode slurry coating process is also carried out in steps to ensure that the pore filler protrusion texture on the surface after the bottom is cleaned is not destroyed; thereby, both sides of the electrode current collector surface are provided with an electrode layer with a low tortuosity pore structure, which is more conducive to the performance of the porous electrode.
[0025] Preferably, the method of performing a first etching on the surface of any side of the electrode current collector comprises:
[0026] The protective film is transferred to the surface to be etched of the electrode current collector, and the preset holes are etched.
[0027] In the first etching method provided by the present invention, the transfer protective film has regularly arranged holes, thereby realizing the etching of the preset holes on the surface of the electrode current collector, and the type of the transfer protective film is selected by conventional technology, such as a photoresist protective film.
[0028] In addition, the present invention does not limit the etching method, and the present invention is applicable to any method that can achieve non-through hole etching on the surface of the electrode current collector.
[0029] Exemplarily, the present invention provides a method for etching a preset hole:
[0030] The surface to be etched of the electrode current collector printed with the protective film is immersed in an etching solution for etching to obtain an electrode current collector structure with preset holes.
[0031] Optionally, the etching solution comprises ferric chloride, hydrogen peroxide and water, wherein the mass concentration of ferric chloride is 30% to 40%, the mass concentration of hydrogen peroxide is 15% to 20%, and the balance is water.
[0032] Optionally, the etching time is 10 min to 2 h, for example, 10 min, 30 min, 60 min, 1.5 h or 2 h.
[0033] Preferably, the aperture size a of the preset hole is 0.01mm~0.1mm, for example 0.01mm, 0.02mm, 0.03mm, 0.04mm, 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm or 0.1mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, with the thickness direction perpendicular to the electrode current collector as the horizontal direction, the hole center distance b of adjacent preset holes in the same horizontal direction is 5a to 10a, for example, 5a, 5.5a, 6a, 6.5a, 7a, 7.5a, 8a, 8.5a, 9a, 9.5a or 10a, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] The preset holes of the electrode current collector provided by the present invention avoid overlapping holes by adjusting the pore size a to 0.01mm-0.1mm and / or the hole center distance b to 5a-10a, and avoid the problem of too many holes, which makes the electrode current collector insufficiently supported and causes structural collapse; and the ordered hole structure is more conducive to subsequent filling with a filling agent; and the plane shape of the hole structure in the present invention is arbitrary, and the shape of the small holes includes but is not limited to square, diamond, circular or elliptical, etc.
[0036] Preferably, along the thickness direction of the electrode collector, the thickness of the electrode collector in the hole area is 0.006 mm to 0.016 mm, for example, 0.006 mm, 0.007 mm, 0.008 mm, 0.009 mm, 0.01 mm, 0.011 mm, 0.012 mm, 0.013 mm, 0.014 mm, 0.015 mm or 0.016 mm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] It should be noted that the electrode current collector in the present invention can be either a positive electrode current collector or a negative electrode current collector, and those skilled in the art can make adaptive selections and adjustments based on actual needs; and regardless of whether a single-sided first etching or a double-sided first etching is performed, a non-through hole structure is obtained, that is, the electrode current collector in the hole area is ensured to have a certain thickness, and the thickness value is adjusted to 0.006mm~0.016mm, which is more conducive to the rapid conduction of electrons at the electrode, so that electrons do not become a limiting step in the electrochemical reaction, and do not occupy too much filling space for the active substance.
[0038] Furthermore, when the electrode collector is a positive electrode collector, the thickness of the electrode collector in the hole region is 0.01 mm to 0.016 mm; when the electrode collector is a negative electrode collector, the thickness of the electrode collector in the hole region is 0.006 mm to 0.012 mm.
[0039] Preferably, the softening point of the pore filling agent is 95°C to 100°C, such as 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the pore filling agent comprises paraffin, preferably chlorinated paraffin.
[0041] In the present invention, paraffin is selected as a filler. On the one hand, it has low viscosity and is easy to level. On the other hand, it will not affect the normal performance of the electrode and will not react with any substance in the electrode. The paraffin in the present invention includes any one or a combination of at least two of microcrystalline paraffin, chlorinated paraffin, liquid paraffin or polyethylene wax; and the grades of paraffin include but are not limited to 52, 54, 56, 58, 60, 62, 64, 66, 68 or 70, etc.; further, chlorinated paraffin is selected as a pore filler, which has a lower viscosity (650-850mpa.s) and better leveling performance. It can quickly penetrate and fill tiny holes through the capillary principle, and ordinary non-aqueous solvents are difficult to replace.
[0042] Preferably, after the second etching treatment is performed on any side of the electrode current collector, the height of the protrusion of the hole filler is 0.1mm to 0.2mm, for example, 0.1mm, 0.11mm, 0.12mm, 0.13mm, 0.14mm, 0.15mm, 0.16mm, 0.17mm, 0.18mm, 0.19mm or 0.2mm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] It should be noted that the present invention does not specifically limit the second etching method, and the present invention is applicable to any method of obtaining a hole filler protrusion; for example, the etchant of the first etching stage can be used to etch the electrode current collector in the non-hole filler area by dripping; the hole filler can form a hard protrusion structure with excellent ductility and pressure resistance at room temperature.
[0044] In the present invention, the height of the protrusion of the hole filler after the second etching is regulated to be 0.1mm~0.2mm, which is the thickness of the electrode layer in the porous electrode after the preset electrode is rolled or slightly lower than the thickness of the electrode layer after rolling, which meets the preparation requirements of the electrode layer of the thick electrode and can better realize the formation of a pore structure with low tortuosity in the electrode layer area of the electrode structure.
[0045] Preferably, the method of performing reverse filling treatment on any side of the electrode current collector comprises:
[0046] The reverse filling agent is used to reversely fill the surface of the electrode current collector with the pore-filling agent protrusions.
[0047] Preferably, the backfilling agent comprises a water-soluble plastic, preferably polyvinyl alcohol.
[0048] In the present invention, reverse filling is performed by water-soluble plastic to fill the concave surface of the surface with the pore-filling agent protrusions into a supporting plane, which can prevent the micro-textures composed of the pore-filling agent protrusions from being destroyed by subsequent roller passing, winding and reprocessing processes.
[0049] Preferably, the method for performing bottom cleaning treatment on any side of the electrode current collector to be used comprises:
[0050] The surface of the electrode current collector to be used on the side to be cleaned is washed with water to remove the reverse filling agent and expose the pore filling agent protrusions.
[0051] Preferably, the temperature of the water washing treatment is 90°C to 100°C, for example, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, after coating the electrode slurry on any side of the electrode current collector, a baking treatment is performed to obtain the electrode to be treated.
[0053] Preferably, the baking treatment temperature is 80°C to 100°C, for example 80°C, 83°C, 85°C, 88°C, 90°C, 93°C, 95°C, 98°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] The temperature of the conditioning and baking treatment of the present invention is 80° C. to 100° C., which can achieve the removal of water in the slurry and avoid the softening of the protruding structure of the hole filling agent and the melting of the reverse filling plane.
[0055] Preferably, the method for removing the pore filling agent comprises:
[0056] The electrode to be treated is subjected to a first heat treatment, roll pressing, dissolution elution and drying.
[0057] In the present invention, the softening of the protrusions of the hole filler is achieved through the first heat treatment, and the softened hole filler still has strong ductility and compression resistance. Further, through the roller pressing treatment, the compaction of the electrode layer and the initial formation of the holes are achieved, and the roller pressing treatment will not cause the softened hole filler to be crushed and broken. When the hole filler is removed by dissolving and eluting, the holes will not collapse and be backfilled and blocked; thereby, the obtained hole structure is complete, the tortuosity is low, and the strength is high.
[0058] Preferably, the temperature of the first heat treatment is 105°C to 110°C, for example, 105°C, 106°C, 107°C, 108°C, 109°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In the present invention, the temperature of the first heat treatment is controlled to 105°C to 110°C, which can not only soften the protrusions of the hole filling agent, but also ensure that even after the subsequent rolling treatment, the softened hole filling agent will still occupy the space of the coated electrode layer, and the ductility and compression resistance will be enhanced, and crushing and rupture will not occur, thereby avoiding the subsequent collapse and backfilling of the holes.
[0060] Preferably, the time of the first heat treatment is 30 min to 1 h, for example 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 1 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] Preferably, the dissolving and eluting method comprises: placing in a remover solution for immersion treatment.
[0062] Preferably, the stripping agent solution comprises tetrahydrofuran and / or propylene carbonate.
[0063] After the dissolution and elution treatment, the pore filling agent in the electrode layer is dissolved and removed by the removing agent; and tetrahydrofuran and / or propylene carbonate are preferably used as the removing agent, which can be used as the solvent component of the electrolyte, so that the pore filling agent can be removed without reacting with the electrode layer, thereby avoiding dissolution and peeling of the electrode layer.
[0064] Furthermore, when the remover solution in the present invention contains tetrahydrofuran and propylene carbonate at the same time, the mass ratio of tetrahydrofuran to propylene carbonate is (50-80):(50-20), for example, 50:50, 55:45, 60:40, 65:35, 70:30, 75:25 or 80:20, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] Preferably, the dissolution and elution temperature is 50°C to 60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] Preferably, the dissolution and elution time is 3 h to 4 h, such as 3 h, 3.5 h or 4 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] Preferably, the electrode after the roll pressing process is subjected to vacuum baking process.
[0068] The present invention performs vacuum baking after the roll pressing process to remove a portion of the pore filling agent and preliminarily forms a hollow, low-tortuosity pore structure in the electrode layer.
[0069] Preferably, the temperature of the vacuum baking treatment is 120°C to 130°C, for example, 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] Preferably, the vacuum degree of the vacuum baking is 10Pa~20Pa, for example 10Pa, 11Pa, 12Pa, 13Pa, 14Pa, 15Pa, 16Pa, 17Pa, 18Pa, 19Pa or 20Pa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] It should also be noted that the porous electrode provided by the present invention includes a positive porous electrode and / or a negative porous electrode, and those skilled in the art can make adaptive selections and adjustments based on actual needs.
[0072] When the porous electrode is a positive porous electrode, the electrode current collector is a positive current collector, and the electrode slurry is a positive electrode slurry; when the porous electrode is a negative porous electrode, the electrode slurry is a negative electrode slurry.
[0073] The present invention has no particular restrictions on the positive electrode current collector and the negative electrode current collector, as long as they are conductive and do not cause chemical changes in the battery. Specifically, the positive electrode current collector or the negative electrode current collector includes but is not limited to copper, stainless steel, aluminum, nickel, titanium, and any one of metal current collectors with carbon or other substances treated on the surface, such as the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil. The shapes of the positive electrode current collector and the negative electrode current collector include but are not limited to metal foil, metal grid, metal mesh, etc. Users can choose according to actual needs, and no specific restrictions are made here.
[0074] The positive electrode slurry includes a positive electrode active material, a conductive agent, a binder, a solvent, etc., wherein the mass ratio of the positive electrode active material, the conductive agent and the binder can be (80-99):(1-10):(1-10).
[0075] The negative electrode slurry includes a negative electrode active material, a conductive agent, a binder, a solvent, etc., wherein the mass ratio of the negative electrode active material, the conductive agent and the binder can be (80-99):(1-10):(1-10).
[0076] The present invention has no particular limitation on the positive electrode active material, which includes but is not limited to: lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (LiNi x Mn y Co 1-x-y O2, referred to as NMC), lithium nickel cobalt aluminum oxide (LiNiCoAlO2, referred to as NCA), lithium manganese oxide (LiMn2O4), lithium manganese iron phosphate (LiMn x Fe 1-x PO4, referred to as LMFP), lithium vanadium phosphate (Li3V2(PO4)3), lithium vanadium phosphate (LiVOPO4), lithium iron phosphate (LiFePO4), lithium titanate (Li2TiO3) and one or more of lithium-rich manganese-based materials.
[0077] The present invention has no particular limitation on the negative electrode active material, which includes but is not limited to: lithium metal and / or lithium alloy; silicon-based negative electrode active materials, which contain silicon, such as silicon alloy, silicon oxide or a combination thereof, which may also be mixed with graphite in some cases; carbonaceous-based negative electrode active materials, which contain one or more of graphite, graphene, carbon nanotubes (CNT) and a combination thereof; lithium titanium oxide (Li4Ti5O 12 ), one or more transition metals (such as tin (Sn)), one or more metal oxides (such as vanadium oxide (V2O5), tin oxide (SnO), titanium dioxide (TiO2)), titanium niobium oxide (Ti x Nb y O z, where 0≤x≤2, 0≤y≤24 and 0≤z≤64), a metal alloy such as copper tin alloy (Cu6Sn5) and one or more metal sulfides such as iron sulfide (FeS).
[0078] The conductive agent is mainly used to assist and improve the conductivity in lithium-ion batteries. The present invention does not particularly limit the specific type of the conductive agent, as long as it has conductivity and does not cause chemical changes. Exemplarily, the conductive agent can include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and one or more of polyphenylene derivatives.
[0079] The present invention has no particular restriction on the specific type of the binder, which includes but is not limited to: one or more of polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, and lithium alginate.
[0080] The present invention has no particular limitation on the specific type of solvent, which includes but is not limited to: at least one of water, acetone, acetonitrile, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, anisole, pyridine, methanol, and ethylene glycol.
[0081] It can be understood that the above description is merely an illustrative example rather than a limitation of the scope of protection. The present invention has no special requirements for the above-mentioned current collector, active material, binder, conductive agent and dissolution. Without violating the inventive concept of the present application, any known material that can be used in the electrode structure of a lithium-ion battery is applicable to the present application; and those skilled in the art can adaptively select and adjust the types according to the different requirements of the positive and negative terminals.
[0082] In a second aspect, the present invention provides a porous electrode, wherein the porous electrode is prepared by the preparation method described in any one of the first aspects;
[0083] The porous electrode comprises an electrode current collector and an electrode active material layer having a porous structure located on at least one side surface of the electrode current collector; the pore structure of the porous structure is arranged perpendicular to the thickness direction of the porous electrode.
[0084] The porous electrode structure provided by the present invention has controllable shape and size, so that the battery capacity can be unaffected, and the obtained pore structure is perpendicular to the thickness direction of the porous electrode, so that the electrolyte can penetrate easily and quickly in the vertical direction of the electrode, thereby accelerating the ion transmission speed; and the thickness of the porous electrode layer can be set according to demand, even if it is a thick electrode structure (single layer thickness of the electrode layer ≥100μm), the electron transmission speed will not be affected.
[0085] Preferably, the diameter of the pore structure in the electrode active material layer is 0.01 mm to 0.1 mm, for example, 0.01 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm or 0.1 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] Preferably, along the thickness direction of the electrode current collector, the center distance of the pore structure in the electrode active material layer is 0.05mm~1mm, for example, 0.05mm, 0.08mm, 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm or 1mm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0087] In a third aspect, the present invention further provides a battery, comprising the porous electrode as described in the second aspect.
[0088] The battery provided by the present invention is applicable to all types of batteries that require thick electrode porous structures, such as lithium ion batteries or sodium ion batteries, etc., and those skilled in the art can make adaptive selections and adjustments based on actual needs.
[0089] Compared with the prior art, the present invention has the following beneficial effects:
[0090] (1) The preparation method provided by the present invention, through the coordinated cooperation of the first etching, the filling treatment and the second etching, obtains a hole structure with a non-through structure along the thickness direction of the electrode current collector after the first etching, and after the hole filling treatment of the hole filling agent, the area in the electrode current collector that does not contain the hole filling agent is subjected to the second etching, thereby obtaining a hole filling agent protrusion with strong ductility and compressive resistance, which will not collapse even after electrode slurry coating and subsequent electrode preparation treatment processes. After removing the hole filling agent, the hole structure with low tortuosity is retained, and the preparation of a low-tortuosity porous electrode is truly realized. It is operable and efficient, and can also be mass-produced, solving the problems of capacity, rate and cycle performance of thick electrodes caused by ion transport limitations; and the preparation method is suitable for actual battery production processes, and the shape and size of the electrode are controllable.
[0091] (2) The porous electrode structure provided by the present invention has controllable shape and size, so that the battery capacity is not affected, and the obtained pore structure is perpendicular to the thickness direction of the porous electrode, so that the electrolyte can penetrate easily and quickly in the direction perpendicular to the electrode, thereby accelerating the ion transmission speed; and the thickness of the porous electrode layer can be set according to demand, even if it is a thick electrode structure (single layer thickness of the electrode layer ≥100μm), the electron transmission speed will not be affected. BRIEF DESCRIPTION OF THE DRAWINGS
[0092] Figure 1 and Figure 2 The preparation process and structural diagram of step (1) of Example 1.
[0093] Figure 3 The preparation process and structural diagram of step (2) in Example 1.
[0094] Figure 4 The preparation process and structural diagram of step (3) in Example 1.
[0095] Figure 5 The preparation process and structural diagram of step (4) in Example 1.
[0096] Figure 6 The preparation process and structural diagram of step (5) in Example 1.
[0097] Figure 7 The preparation process and structural diagram of step (6) in Example 1.
[0098] Figure 8 The preparation process and structural diagram of step (7) in Example 1.
[0099] Fig. 9 The preparation process and structural diagram of step (8) in Example 1.
[0100] Fig.10 The preparation process and structural diagram of step (9) in Example 1.
[0101] Fig.11 The preparation process and structural diagram of step (10) in Example 1.
[0102] Fig.12 The preparation process and structural diagram of step (11) in Example 1.
[0103] Fig.13 The diagram shows the preparation process and structure of step (12) in Example 1.
[0104] Fig.14 Schematic diagram of the porous negative electrode with a porous structure finally obtained in Example 1.
[0105] Among them, 1-copper foil, 2-preset small hole, 21-hole, 3-paraffin column, 4-photoresist, 5-powder layer, 51-powder layer after rolling, 7-concave surface, 8-polyvinyl alcohol. DETAILED DESCRIPTION
[0106] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0107] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0108] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0109] Example 1
[0110] This embodiment provides a method for preparing a porous negative electrode, and the preparation method is as follows:
[0111] (1) Pad printing protective film: Figure 1 and Figure 2As shown, the photoresist 4 is covered on both sides of the copper foil 1 by pad printing to form a surface layer with preset small holes 2 arranged in a certain pattern with a certain interval b and a certain aperture a; the aperture a of the preset small holes 2 is 0.1 mm, and the interval b is 5a=0.5 mm of the aperture a of the preset small holes 2;
[0112] (2) First etching of copper foil 1: Figure 3 As shown, the copper foil 1 with the protective film printed thereon is immersed in the etching solution of the copper clad laminate (the etching solution contains 35% by mass of ferric chloride, 15% by mass of hydrogen peroxide and water) for etching for 2 hours, so that the surfaces of both sides of the copper foil 1 have non-through holes 21, and the thickness c of the copper foil 1 in the hole 21 area is 0.006 mm, thereby obtaining the copper foil 1 with holes;
[0113] (3) Filling treatment of pore filling agent: Figure 4 As shown, the copper foil 1 with the holes 21 etched therein is immersed in a molten chlorinated paraffin 70 solution by dip coating, so that the paraffin fills the holes 21 to form paraffin columns 3, and the paraffin columns 3 just fill the holes 21 and are flush with the outer surface of the foil 1;
[0114] (4) Second etching of the surface A on one side of the copper foil 1: Figure 5 As shown, the etching solution of the copper clad laminate in step (2) is dripped onto the A surface of the filled copper foil 1 for a second etching, and the copper foil 1 on the A surface is etched except for the area occupied by the wax column 3 until only a certain thickness of the copper foil 1 is retained, and then it is washed and dried with water, forming the copper foil 1 on the A surface with raised patterns (hole filling agent raised patterns) composed of the wax column 3 and the concave surface 7; the height of the raised patterns composed of the wax column 3 is 0.2 mm;
[0115] (5) Reverse filling of side A: Figure 6 As shown, the etched copper foil 1 is directly poured into the molten polyvinyl alcohol 8 to perform reverse filling and leveling treatment, so that the polyvinyl alcohol 8 covers the entire A surface and is flush with the paraffin column 3;
[0116] (6) The second etching of the other side surface B of the copper foil 1: Figure 7 As shown, the copper foil 1 with reverse filling on the A side is immersed in the etching solution of the copper clad laminate in step (2) again for etching, and the copper foil 1 on the B side is etched except for the area occupied by the paraffin column 3 until only a certain thickness of the copper foil 1 is retained, and then it is washed with water and dried;
[0117] (7) Reverse filling of side B: Figure 8 As shown, the B surface of the etched copper foil 1 is directly poured into molten polyvinyl alcohol 8 for reverse filling and leveling treatment, so that the polyvinyl alcohol 8 covers the entire B surface and is flush with the paraffin column 3, thereby obtaining a copper foil 1 with reverse filling planes on both sides;
[0118] (8) Clear the bottom of side A: Fig. 9 As shown, before the negative electrode slurry is coated, the A surface of the copper foil 1 is first washed with hot water at 100°C. Since the polyvinyl alcohol 8 is highly soluble in water, the polyvinyl alcohol 8 layer is completely dissolved and removed after washing and dissolving with water. At this time, the copper foil 1 plane formed by the texture of the convex wax column 3 and the concave surface 7 is re-formed;
[0119] (9) A side slurry coating: Fig.10 As shown, immediately after the A surface is cleaned, the A surface of the copper foil 1 is passed through a transfer coating machine for lithium batteries, and negative electrode slurry is transferred and coated according to the required coating amount, and the negative electrode slurry is coated on the concave surface 7 of the copper foil 1 to form a slurry layer, which is then baked and dried to form an electrode sheet with an A surface slurry layer 5 and a B surface polyvinyl alcohol 8;
[0120] Among them, negative electrode slurry: graphite (graphite is a single particle prepared from isotropic coke), conductive carbon black, CMC thickener and SBR binder are mixed in a mass ratio of 95.5:1:1.5:2, and deionized water is added to mix to obtain negative electrode slurry;
[0121] (10) Cleaning the bottom of side B: Fig.11 As shown, when positive and negative electrode coating is required, the B surface of the copper foil 1 is first washed with hot water at 100°C to remove the polyvinyl alcohol 8, and then the copper foil 1 plane formed by the texture of the raised wax column 3 and the concave surface 7 is re-formed;
[0122] (11) B side slurry coating: Fig.12 As shown, immediately after the B surface is cleaned, the B surface of the copper foil 1 is passed through a transfer coating machine for lithium batteries, and transfer coating is performed according to the required coating amount, and the negative electrode slurry is coated on the concave surface 7 of the copper foil 1 to form a slurry layer, and then baked and dried to form an electrode sheet with the A surface and the B surface both filled with the powder layer 5, thereby obtaining an electrode to be processed;
[0123] Among them, negative electrode slurry: graphite (graphite is a single particle prepared from isotropic coke), conductive carbon black, CMC thickener and SBR binder are mixed in a mass ratio of 95.5:1:1.5:2, and deionized water is added to mix to obtain negative electrode slurry;
[0124] (12) Electrode rolling hole support: Heat the electrode to be treated in an oven at 110°C for 30 min to soften the paraffin column 3. Fig.13 As shown, the powder layer 5 is then put into a roller press for roller pressing, and the powder layer 5 is compressed by a steel rod to obtain a rolled powder layer 51, and the initial thickness changes from e to d;
[0125] (13) Dewaxing and pore formation of electrode: After rolling, the electrode is vacuum baked at a temperature of 125°C and a vacuum degree of 15Pa for 6 hours to remove most of the paraffin in the paraffin column 3, forming hollow holes with a diameter of 0.1 mm and a spacing of 0.5 mm; the electrode is immersed in a mixture of tetrahydrofuran and propylene carbonate (a dewaxing agent solution, in which the mass ratio of tetrahydrofuran to propylene carbonate is 65:35) at 55°C for 4 hours, at which time the paraffin in the holes is completely dissolved, and then dried to obtain the following: Fig.14 The porous negative electrode with a porous structure shown in the figure comprises a copper foil 1 and a negative electrode active material layer with a porous structure located on both sides of the copper foil 1; the pore structure of the porous structure is arranged perpendicular to the thickness direction of the porous negative electrode.
[0126] Example 2
[0127] This embodiment provides a method for preparing a porous negative electrode, and the preparation method is as follows:
[0128] (1) Pad printing protective film: a photoresist is applied to both sides of the copper foil by pad printing to form a surface layer with predetermined small holes arranged in a certain pattern with a certain interval b and a certain aperture a; the aperture a of the predetermined small holes is 0.01 mm, and the interval b is 10a=0.1 mm of the aperture a of the predetermined small holes;
[0129] (2) First etching of copper foil 1: The copper foil with the protective film printed thereon is immersed in the etching solution of the copper clad laminate (the etching solution contains 35% by mass of ferric chloride, 15% by mass of hydrogen peroxide and water) for etching for 10 min, so that non-through holes are formed on both sides of the copper foil, and the thickness c of the copper foil in the hole area is 0.016 mm, thereby obtaining a copper foil with holes;
[0130] (3) Filling treatment with a hole-filling agent: The copper foil with the holes etched is immersed in a molten chlorinated paraffin 70 solution by dip coating, so that the paraffin fills the holes to form a paraffin column, which just fills the holes and is flush with the outer surface of the foil;
[0131] (4) Second etching of the surface A of one side of the copper foil: drip the etching solution of the copper clad laminate in step (2) onto the surface A of the filled copper foil for second etching, and etch the copper foil on the surface A except the area occupied by the wax column until only a certain thickness of copper foil is retained, and then wash and dry with water to form a protrusion pattern (hole filling agent protrusion) composed of wax columns and a concave copper foil on the surface A; the height of the protrusion composed of the wax columns is 0.1 mm;
[0132] (5) Reverse filling of surface A: Pour molten polyvinyl alcohol directly into the etched surface A of the copper foil for reverse filling, so that the polyvinyl alcohol covers the entire surface A and is flush with the paraffin column;
[0133] (6) The second etching of the other side of the copper foil surface B: Figure 7 As shown, the copper foil with reverse filling on the A side is immersed in the etching solution of the copper-clad laminate in step (2) again for etching, and the copper foil on the B side is etched except for the area occupied by the paraffin column until only a certain thickness of copper foil is retained, and then it is washed with water and dried;
[0134] (7) Reverse filling of the B side: Pour molten polyvinyl alcohol directly into the B side of the etched copper foil for reverse filling treatment, so that the polyvinyl alcohol covers the entire B side and is flush with the paraffin column, thereby obtaining a copper foil with reverse filling planes on both sides;
[0135] (8) Cleaning the bottom of the A side: Before coating the negative electrode slurry, the A side of the copper foil is first cleaned with hot water at 90°C. Since polyvinyl alcohol is highly soluble in water, the polyvinyl alcohol layer is completely dissolved and removed after washing with water. At this time, the copper foil plane formed by the texture of the raised wax columns and the concave surface is re-formed;
[0136] (9) A-side slurry coating: Immediately after the A-side bottom is cleaned, the A-side of the copper foil is passed through a lithium battery transfer coating machine, and the negative electrode slurry is transferred and coated on the concave surface of the copper foil to form a slurry layer, which is then baked and dried to form an electrode sheet with a slurry layer on the A-side and polyvinyl alcohol on the B-side;
[0137] Among them, negative electrode slurry: graphite (graphite is a single particle prepared from isotropic coke), conductive carbon black, CMC thickener and SBR binder are mixed in a mass ratio of 95.5:1:1.5:2, and deionized water is added to mix to obtain negative electrode slurry;
[0138] (10) B-side cleaning: When positive and negative electrode coating is required, the B-side of the copper foil is first cleaned with 90°C hot water to remove the polyvinyl alcohol. At this time, the copper foil 1 plane formed by the texture of the raised wax columns and the concave surface is re-formed;
[0139] (11) B side slurry coating: Fig.12 As shown, immediately after the B side is cleaned, the B side of the copper foil is passed through a transfer coating machine for a lithium battery, and transfer coating is performed according to the required coating amount, and the negative electrode slurry is coated on the concave surface of the copper foil 1 to form a slurry layer, and then baked and dried to form an electrode sheet with a powder layer filled on both the A side and the B side, thereby obtaining an electrode to be processed;
[0140] Among them, negative electrode slurry: graphite (graphite is a single particle prepared from isotropic coke), conductive carbon black, CMC thickener and SBR binder are mixed in a mass ratio of 95.5:1:1.5:2, and deionized water is added to mix to obtain negative electrode slurry;
[0141] (12) Electrode roll-pressing hole support: The electrode to be processed is first heated in an oven at 105°C for 30 min to soften the paraffin column, and then placed in a roller press for rolling. The powder layer is compressed by a steel rod, and the initial thickness of the thinner powder layer changes from e to d;
[0142] (13) Dewaxing and pore formation of electrode: After rolling, the electrode is vacuum-baked at 130°C and 10Pa for 6 hours to remove most of the paraffin in the paraffin column and form hollow holes with a diameter of 0.01mm and a spacing of 0.1mm; the electrode is immersed in a mixture of tetrahydrofuran and propylene carbonate (a remover solution, in which the mass ratio of tetrahydrofuran to propylene carbonate is 65:35) at 60°C for 3 hours, at which time the paraffin in the holes is completely dissolved, and then dried to obtain a porous negative electrode with a porous structure; the porous negative electrode includes a copper foil and a negative electrode active material layer with a porous structure located on both sides of the copper foil; the pore structure of the porous structure is arranged perpendicular to the thickness direction of the porous negative electrode.
[0143] Example 3
[0144] This embodiment provides a method for preparing a porous negative electrode, and the preparation method is as follows:
[0145] (I) Pad printing protective film: a photoresist is covered on one side of the copper foil by pad printing to form a surface layer with small holes arranged in a certain pattern with a certain interval b and a certain aperture a; the aperture a of the small holes is 0.1 mm, and the interval b is 5a of the aperture a of the small holes;
[0146] (II) First etching of copper foil: The copper foil 1 with the protective film printed thereon is immersed in an etching solution of a copper-clad laminate (the etching solution contains 35% by mass of ferric chloride, 15% by mass of hydrogen peroxide and water) for etching for 2 h, so that a single-side surface of the copper foil 1 has non-through holes, and the thickness c of the copper foil in the hole region is 0.006 mm, thereby obtaining a copper foil with holes;
[0147] (III) Filling treatment with a hole-filling agent: The copper foil with the holes etched is immersed in a molten chlorinated paraffin 70 solution by dip coating, so that the paraffin fills the holes to form a paraffin column, which just fills the holes and is flush with the outer surface of the foil;
[0148] (IV) Second etching of the surface of the copper foil hole filler side: dripping the etching solution of the copper clad laminate in step (2) onto the A side of the filled copper foil for second etching, etching the copper foil except the area occupied by the wax column until only a certain thickness of the copper foil base is retained, and then washing and drying with water to form a protrusion pattern composed of wax columns (hole filler protrusion) and a concave copper foil; the height of the protrusion composed of wax columns is 0.2 mm;
[0149] (V) Slurry coating: Place the side of the copper foil with the paraffin column into a transfer coating machine for lithium batteries, and perform negative electrode slurry transfer coating according to the required coating amount, apply the negative electrode slurry to the concave surface of the copper foil to form a slurry layer, and then bake and dry the slurry layer to obtain an electrode to be processed;
[0150] Among them, negative electrode slurry: graphite (graphite is a single particle prepared from isotropic coke), conductive carbon black, CMC thickener and SBR binder are mixed in a mass ratio of 95.5:1:1.5:2, and deionized water is added to mix to obtain negative electrode slurry;
[0151] (VI) Electrode roll-pressing hole support: The electrode to be processed is first heated in an oven at 110°C for 30 min to soften the paraffin column, and then put into a roller press for rolling. The powder layer is compressed by a steel rod, and the thinner the powder layer, the thinner the initial thickness;
[0152] (VII) Dewaxing and pore formation of the electrode: After rolling, the electrode is vacuum-baked at a temperature of 125°C and a vacuum degree of 15Pa for 6 hours to remove most of the paraffin in the paraffin column and form hollow holes with a diameter of 0.1mm and a spacing of 0.5mm; the electrode is immersed in a mixture of tetrahydrofuran and propylene carbonate (a remover solution, in which the mass ratio of tetrahydrofuran to propylene carbonate is 65:35) at 55°C for 4 hours, at which time the paraffin in the holes is completely dissolved, and then the electrode is dried to obtain a porous negative electrode with the porous structure shown in the figure; the porous negative electrode includes a copper foil and a negative electrode active material layer with a porous structure located on a single side surface of the copper foil; the pore structure of the porous structure is arranged perpendicular to the thickness direction of the porous negative electrode.
[0153] Example 4
[0154] The difference between this embodiment and embodiment 1 is that the aperture a of the small hole 2 in step (1) of this embodiment is 0.005 mm.
[0155] The rest of the preparation methods and parameters were the same as those in Example 1.
[0156] Example 5
[0157] The difference between this embodiment and embodiment 1 is that the aperture a of the small hole 2 in step (1) of this embodiment is 0.15 mm.
[0158] The rest of the preparation methods and parameters were the same as those in Example 1.
[0159] Example 6
[0160] The difference between this embodiment and embodiment 1 is that the pore filling agent in step (3) of this embodiment is microcrystalline wax 70.
[0161] The rest of the preparation methods and parameters were the same as those in Example 1.
[0162] Example 7
[0163] The difference between this embodiment and embodiment 1 is that the cleaning temperature in step (8) and step (10) in this embodiment is 105°C.
[0164] The rest of the preparation methods and parameters were the same as those in Example 1.
[0165] Example 8
[0166] The difference between this embodiment and embodiment 1 is that step (12) of this embodiment is modified as follows: the electrode to be processed is placed in a roller press for roller pressing, the powder layer 5 is compressed by a steel rod, a thinner powder layer 51 is generated, and the initial thickness is changed from e to d, and then heated in an oven at 110° C. for 30 minutes to soften the paraffin column 3;
[0167] That is, the first heat treatment step and the rolling step are exchanged.
[0168] The rest of the preparation methods and parameters were the same as those in Example 1.
[0169] Example 9
[0170] The difference between this embodiment and embodiment 1 is that in step (13) of this embodiment, the electrode sheet after rolling in step (12) is directly immersed in a mixture of tetrahydrofuran and propylene carbonate at 55° C. for 4 hours;
[0171] That is, the dissolution and elution process is directly carried out without vacuum baking.
[0172] The rest of the preparation methods and parameters were the same as those in Example 1.
[0173] Example 10
[0174] The difference between this embodiment and embodiment 1 is that in this embodiment, the copper foil is replaced by aluminum foil;
[0175] The etching solution is a mixed solution of 30% FeCl3 by mass, 15% HCl by mass, 0.3% auxiliary agent ammonium cerium nitrate by mass, 0.2% isopropanol by mass and 54.5% water by mass. Etching takes 30 minutes.
[0176] The electrode slurry is replaced with a positive electrode slurry, and the positive electrode slurry is: lithium iron phosphate positive electrode material (LFP), conductive carbon black SP, polytetrafluoroethylene PVDF are mixed evenly with solvent NMP according to a mass ratio of NCM:SP:PVDF of 95:2:2.5 to prepare a positive electrode slurry.
[0177] The rest of the preparation methods and parameters were the same as those in Example 1.
[0178] Comparative Example 1
[0179] This comparative example provides a method for preparing a negative electrode, and the method for preparing the negative electrode is as follows:
[0180] Graphite (graphite is a single particle prepared from isotropic coke), conductive carbon black, CMC thickener and SBR binder are mixed in a mass ratio of 95.5:1:1.5:2, and deionized water is added to obtain a negative electrode slurry;
[0181] The negative electrode slurry was coated on both sides of the copper foil of the same embodiment 1, with a coating thickness of 130 μm on each side, dried, and rolled to obtain the negative electrode.
[0182] Comparative Example 2
[0183] This comparative example provides a method for preparing a porous negative electrode, and the preparation method comprises the following steps:
[0184] (1) Preparation of solid ingredients: Based on the total weight of the solid ingredients as 100%, the raw materials are prepared according to the following weight percentages: 94.5% of graphite (graphite is a single particle prepared from isotropic coke), 1% of conductive carbon black Super P, 1.5% of carboxymethyl cellulose CMC, 2% of styrene-butadiene rubber SBR, and 1.5% of a pore-forming agent, which is a mixed paraffin wax (the mass ratio of octadecane to paraffin wax is 1:1) of a higher alkane with a carbon number greater than 17. The melting point of the pore-forming agent is 60°C.
[0185] (2) Ingredients: Mix deionized water and CMC and stir to obtain glue solution. Add graphite material, Super P and pore-forming agent to 60% glue solution according to the solid content of 65%. After stirring for 2 hours, add the remaining glue solution and stir evenly. Finally, add SBR and water and stir evenly to obtain a slurry with a viscosity of about 2000mPa.s. Slurry coating: The slurry is coated on the surface of the current collector copper foil by transfer coating. The coating thickness is 80μm, and the moisture is removed by baking in a coating oven.
[0186] (3) Preheating with baking roller: The electrode plate with coating layer is preheated by baking roller, and the preheating temperature is 50°C;
[0187] (4) Extraction with extractant: The preheated plates are directly introduced into 35°C dichloromethane for extraction for more than 0.5 to 2 hours;
[0188] (5) Plate baking: The extracted plate is baked in an oven to obtain a porous negative electrode.
[0189] Comparative Example 3
[0190] This comparative example provides a method for preparing a positive electrode, and the preparation method is as follows:
[0191] The positive electrode material (LFP), conductive carbon black SP, polytetrafluoroethylene PVDF were mixed evenly with solvent NMP at a mass ratio of NCM:SP:PVDF of 95:2:2.5 to prepare a positive electrode slurry;
[0192] The positive electrode slurry was coated on both sides of the same aluminum foil as in Example 10, with a coating thickness of 120 μm on each side, dried, and rolled to obtain the positive electrode.
[0193] Comparative Example 4
[0194] This comparative example provides a method for preparing a porous positive electrode, and the preparation method comprises the following steps:
[0195] (1) Prepare solid ingredients: Based on the total weight of the solid ingredients as 100%, prepare the raw materials according to the following weight percentages: 94% of lithium iron phosphate positive electrode material LFP, 2.0% of conductive carbon black Super P, 2.5% of polyvinylidene fluoride PVDF, and 1.5% of a pore-forming agent, which is a mixed paraffin wax (the mass ratio of octadecane to paraffin wax is 1:1) of a higher alkane with a carbon number greater than 17. The melting point of the pore-forming agent is 60°C.
[0196] (2) Preparation: Add LFP, Super P, pore former and N-methylpyrrolidone (NMP) to PVDF at a solid content of 65% to obtain a uniformly mixed slurry with a viscosity of about 6000-8000 mPa.s; Slurry coating: The slurry is coated on the surface of the current collector aluminum foil by transfer coating with a coating thickness of 80 μm, and then baked in a coating oven to remove moisture;
[0197] (3) Preheating with baking roller: The electrode plate with coating layer is preheated by baking roller, and the preheating temperature is 55°C;
[0198] (4) Extraction with extractant: The preheated plates are directly introduced into 35°C dichloromethane for extraction for more than 0.5 to 2 hours;
[0199] (5) Plate baking: The extracted plate is baked in an oven to obtain a porous positive electrode.
[0200] (I) Application of negative electrodes in Examples 1-9 and Comparative Examples 1-2:
[0201] The porous negative electrodes provided in Examples 1-9 and Comparative Examples 1-2 were punched into square sheets of 20 mm*20 mm in a dry environment by a punching machine as the negative electrode, and the metal lithium sheet was punched into a square sheet of 21 mm*21 mm in a glove box as the positive electrode. The isolation membrane selected a ceglar composite film, and a layer of lithium sheet / a layer of diaphragm / a layer of negative electrode / a layer of diaphragm / a layer of lithium sheet were stacked into a core, and then placed in a punched aluminum-plastic film bag, encapsulated on the airbag side, and an electrolyte was added to assemble to obtain a soft-packed graphite-lithium metal half-cell (half-cell 1); the electrolyte was an organic solution obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:50:20, and the concentration of lithium salt (lithium hexafluorophosphate) in the electrolyte was 1.15 mol / L.
[0202] The prepared half-cell 1 was subjected to a performance test under the following test conditions:
[0203] (a) Under normal temperature and voltage conditions of 25°C and 0.1-2.0V, the gram capacity test was carried out at 0.2C.
[0204] (b) Under normal temperature conditions of 25°C and a voltage of 0.1 to 2.0 V, the rate performance test was carried out at a charge rate of 0.2C and a discharge rate of 0.5C, and a rate performance of 0.5C / 0.2 was obtained; the rate performance test was carried out at a charge rate of 0.2C and a discharge rate of 1C, and a rate performance of 1C / 0.2 was obtained; the rate performance test was carried out at a charge rate of 0.2C and a discharge rate of 2C, and a rate performance of 2C / 0.2 was obtained.
[0205] (c) Under normal temperature conditions of 25°C, a charge and discharge cycle test was carried out at a voltage of 0.1-2.0 V and a charge and discharge rate of 0.2C, and the capacity retention rates of 100 cycles, 200 cycles, 300 cycles, 500 cycles and 800 cycles were tested respectively.
[0206] The test results of the above tests are shown in Table 1.
[0207] Table 1
[0208]
[0209]
[0210] (II) Application of the positive electrode provided in Example 10 and Comparative Examples 3-4:
[0211] The positive electrodes provided in Example 10 and Comparative Examples 3-4 were respectively cut into square sheets with a diameter of 21 mm*21 mm in a dry environment by a punching machine as the positive electrode, and the metal lithium sheet was punched into a square sheet of 20 mm*20 mm in a glove box as the negative electrode. The isolation membrane selected a ceglar composite film, and a layer of lithium sheet / a layer of diaphragm / a layer of positive electrode / a layer of diaphragm / a layer of lithium sheet were stacked into a core, and then placed in a punched aluminum-plastic film bag, encapsulated on the airbag side, and an electrolyte was added to assemble a soft-pack lithium iron phosphate-lithium metal half-cell (half-cell 2); the electrolyte was an organic solution obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:50:20, and the concentration of lithium salt (lithium hexafluorophosphate) in the electrolyte was 1.15 mol / L.
[0212] The prepared half-cell 2 was subjected to a performance test under the following test conditions:
[0213] (a) Under normal temperature and voltage conditions of 25°C and 2.5 to 3.65 V, the gram capacity test was performed at 0.2C.
[0214] (b) Under normal temperature conditions of 25°C and a voltage of 2.5-3.65V, the rate performance test was carried out at a charge rate of 0.2C and a discharge rate of 0.5C, and a rate performance of 0.5C / 0.2 was obtained; the rate performance test was carried out at a charge rate of 0.2C and a discharge rate of 1C, and a rate performance of 1C / 0.2 was obtained; the rate performance test was carried out at a charge rate of 0.2C and a discharge rate of 2C, and a rate performance of 2C / 0.2 was obtained.
[0215] (c) Under normal temperature conditions of 25°C, a charge and discharge cycle test was carried out at a voltage of 2.5-3.65V and a charge and discharge rate of 0.2C, and the capacity retention rates of 100 cycles, 200 cycles, 300 cycles, 500 cycles and 800 cycles were tested respectively.
[0216] The test results of the above tests are shown in Table 2.
[0217] Table 2
[0218]
[0219] To sum up, the preparation method provided by the present invention, through the coordinated cooperation of the first etching, the filling treatment and the second etching, obtains a hole structure with a non-through structure along the thickness direction of the electrode current collector after the first etching, and after the hole filling treatment of the hole filling agent, the area in the electrode current collector that does not contain the hole filling agent is subjected to the second etching to obtain a hole filling agent protrusion with strong ductility and compressive resistance, which will not collapse even after electrode slurry coating and subsequent electrode preparation treatment process. After removing the hole filling agent, the hole structure with low tortuosity is retained, and the preparation of low-tortuosity porous electrodes is truly realized. It is operable and efficient, and can also be mass-produced, solving the problems of capacity, rate and cycle performance of thick electrodes caused by ion transport limitations; and the preparation method is suitable for actual battery production processes, and the shape and size of the electrodes are controllable.
[0220] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a porous electrode, characterized in that: The preparation method comprises the following steps: Performing a first etching on at least one side of the electrode current collector to obtain an electrode current collector having holes; Filling the holes in the electrode current collector with a pore-filling agent, and performing a second etching on the area of the electrode current collector that does not contain the pore-filling agent after the filling treatment, so that the electrode current collector has a surface pore-filling agent protrusion, thereby obtaining an electrode current collector to be used; Coating the surface of the electrode current collector to be used with electrode slurry to obtain an electrode to be treated; The pore-filling agent is removed from the electrode to be processed to obtain the porous electrode.
2. The preparation method according to claim 1, characterized in that: After performing the second etching so that the electrode current collector has a surface pore-filling agent protrusion, the surface is reversely filled and leveled to obtain the electrode current collector to be used; Preferably, the electrode current collector to be used for reverse filling treatment is first subjected to bottom cleaning treatment to expose the pore-filling agent protrusions, and then the electrode slurry is coated to obtain the electrode to be treated; Preferably, when both sides of the electrode current collector have surface pore-filling agent protrusions, the preparation method comprises: Firstly, the surfaces of both sides of the electrode current collector are subjected to a first etching and a filling treatment respectively, and then the surface of one side is subjected to a second etching to obtain an electrode current collector having a protrusion of a pore-filling agent on one side of the surface, and then the side surface is subjected to a reverse filling treatment to obtain an electrode current collector having a reverse filling plane on one side; Then, the other side surface of the electrode current collector is further etched for a second time to obtain a hole-filling agent protrusion on the other side surface, and then the side surface is reversely filled and flattened to obtain an electrode current collector with reverse-filled flat surfaces on both sides; The electrode current collector with reverse filling planes on both sides is used as the electrode current collector to be used, and the bottom of one side surface is firstly cleaned and the electrode slurry is coated, and then the bottom of the other side surface is cleaned and the electrode slurry is coated on the other side surface to obtain the electrode to be processed; The pore-filling agent is removed from the electrode to be processed to obtain the porous electrode.
3. The preparation method according to claim 1 or 2, characterized in that: The method of performing a first etching on the surface of any side of the electrode current collector comprises: Transfer the protective film to the surface to be etched of the electrode current collector, and etch the preset holes; Preferably, the aperture size a of the preset hole is 0.01 mm to 0.1 mm; Preferably, with the thickness direction perpendicular to the electrode current collector as the horizontal direction, the hole center distance b of adjacent preset holes in the same horizontal direction is 5a-10a; Preferably, along the thickness direction of the electrode current collector, the thickness of the electrode current collector in the hole region is 0.006 mm to 0.016 mm.
4. The preparation method according to claim 1 or 2, characterized in that: The softening point of the pore filling agent is 95°C to 100°C; Preferably, the pore filling agent comprises paraffin, preferably chlorinated paraffin.
5. The preparation method according to claim 1 or 2, characterized in that: After the second etching process is performed on any side of the electrode current collector, the height of the protrusion of the hole filling agent is 0.1 mm to 0.2 mm.
6. The preparation method according to claim 2, characterized in that: The method of performing reverse filling treatment on any side of the electrode current collector comprises: Using a reverse filling agent to reversely fill and level the surface of the electrode current collector with the pore-filling agent protrusions; Preferably, the reverse filler comprises a water-soluble plastic, preferably polyvinyl alcohol; Preferably, the method for performing bottom cleaning treatment on any side of the electrode current collector to be used comprises: The surface of the electrode current collector to be used on the side to be cleaned is washed with water to remove the reverse filling agent and expose the pore filling agent protrusion; Preferably, the temperature of the water washing treatment is 90°C to 100°C.
7. The preparation method according to claim 1 or 2, characterized in that: After coating any side of the electrode current collector with electrode slurry, baking is performed to obtain the electrode to be processed; Preferably, the baking temperature is 80°C to 100°C.
8. The preparation method according to claim 1 or 2, characterized in that: The method for removing the pore filling agent comprises: The electrode to be treated is subjected to a first heat treatment, roll pressing, dissolution elution and drying; Preferably, the temperature of the first heat treatment is 105°C to 110°C, and the time of the first heat treatment is 30min to 1h; Preferably, the dissolving and eluting method comprises: placing in a remover solution for immersion treatment; Preferably, the stripping agent solution comprises tetrahydrofuran and / or propylene carbonate; Preferably, the dissolution and elution temperature is 50°C to 60°C, and the dissolution and elution time is 3h to 4h; Preferably, the electrode after the roll-pressing process is subjected to a vacuum baking process, the temperature of the vacuum baking process is 120° C. to 130° C., and the vacuum degree of the vacuum baking is 10 Pa to 20 Pa.
9. A porous electrode, characterized in that: The porous electrode is prepared by the preparation method according to any one of claims 1 to 8; The porous electrode comprises an electrode current collector and an electrode active material layer having a porous structure located on at least one side surface of the electrode current collector; the pore structure of the porous structure is arranged perpendicular to the thickness direction of the porous electrode.
10. A battery, characterized in that: The battery comprises the porous electrode of claim 9.